This preview shows pages 1–3. Sign up to view the full content.
This preview has intentionally blurred sections. Sign up to view the full version.
View Full Document
Unformatted text preview: MA341 Homework 7 Solution 4.6 5. y 00 2 y + y = t 1 e t . The characteristic equation for the corresponding homogeneous equation is r 2 2 r + 1 = 0; it has a double root: r = 1. Thus, e t and te t are two linearly independent solutions to the homogeneous equation. Then, we take y p ( t ) = v 1 ( t ) e t + v 2 ( t ) te t , and, referring to formula (9) in section 4.6, solve the system v 1 ( t ) e t + v 2 ( t ) te t = 0 , v 1 ( t ) e t + v 2 ( t )( e t + te t ) = t 1 e t , for v 1 ( t ) and v 2 ( t ). This yields: v 1 ( t ) = 1 , v 2 ( t ) = t 1 . Integrating, we obtain: v 1 ( t ) = Z 1 dt = t + C 1 , v 2 ( t ) = Z t 1 dt = ln  t  + C 2 . We need only one particular solution, so we take both C 1 and C 2 to be zero for simplicity. Then, substituting v 1 ( t ) and v 2 ( t ) into y p ( t ), we obtain: y p ( t ) = te t + ln  t  te t . The first term on the righthand side of the previous equality is a part of the general solution to the homogeneous equation. Consequently, a general solution to the given inhomogeneous equation can be taken in the form: y ( t ) = C 1 e t + C 2 te t + ln  t  te t . 9. y 00 + 4 y = csc 2 (2 t ) . The characteristic equation for the corresponding homogeneous equation is r 2 +4 = 0; it has two complexconjugate roots: r = ± 2 i . Thus, cos 2 t and sin 2 t are two linearly independent solutions to the homogeneous equation. Then, we take y p ( t ) = v 1 ( t ) cos 2 t + v 2 ( t ) sin 2 t, and, referring to formula (9) in section 4.6, solve the system (cos 2 t ) v 1 ( t ) + (sin 2 t ) v 2 ( t ) = 0 , ( 2 sin 2 t ) v 1 ( t ) + (2 cos 2 t ) v 2 ( t ) = csc 2 (2 t ) , for v 1 ( t ) and v 2 ( t ). This yields: v 1 ( t ) = 1 2 csc(2 t ) , 1 MA341 Homework 7 Solution v 2 ( t ) = 1 2 cos 2 t csc 2 (2 t ) . Integrating, we obtain: v 1 ( t ) = Z 1 2 csc(2 t ) dt = 1 4 ln  csc(2 t ) + cot(2 t )  + C 1 , v 2 ( t ) = Z 1 2 cos 2 t csc 2 (2 t ) dt = 1 4 Z 1 sin 2 (2 t ) d (sin 2 t ) = 1 4 csc(2 t ) + C 2 . We need only one particular solution, so we take both C 1 and C 2 to be zero for simplicity. Then, substituting v 1 ( t ) and v 2 ( t ) into y p ( t ), we obtain: y p ( t ) = 1 4 [(cos 2 t ) ln  csc(2 t ) + cot (2 t )   1] . Consequently, a general solution to the given equation can be taken in the form: y ( t ) = C 1 cos 2 t + C 2 sin 2 t + 1 4 [(cos 2 t ) ln  csc(2 t ) + cot(2 t )   1] . 11. y 00 + y = tan 2 ( t ) The characteristic equation for the corresponding homogeneous equation is r 2 + 1 = 0; it has two complexconjugate roots: r = ± i . Thus, cos t and sin t are two linearly independent solutions to the homogeneous equation. Then, we take y p ( t ) = v 1 ( t ) cos t + v 2 ( t ) sin t, and, referring to formula (9) in section 4.6, solve the system (cos t ) v 1 ( t ) + (sin t ) v 2 ( t ) = 0 , ( sin t ) v 1 ( t ) + (cos t ) v 2 ( t ) = tan 2 t, for v 1 ( t ) and v 2 ( t ). This yields: v 1 ( t ) = sin 3 t cos 2 t , v 2 ( t ) = sin 2 t cos t ....
View
Full
Document
This homework help was uploaded on 04/16/2008 for the course MA 341 taught by Professor Schecter during the Spring '08 term at N.C. State.
 Spring '08
 Schecter
 Differential Equations, Equations

Click to edit the document details